(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2024)
Theravada (Theravāda), called Pali Buddhism from the language of its canonical texts, and Southern Buddhism from the area where its followers live, is the oldest and still actively present, vital Buddhist tradition. The last twenty years of the 20th century and the first of the 21st century were the period of the Theravada Renaissance, in which monks from the West played a significant role. Theravada is also the longest known Buddhist tradition in Europe. The turn of the 19th and 20th centuries brought the first monastic ordinations of Europeans. At first they were semi-anonymous sailors and travelers. Next, the English occultist Allan Benett (Ananda Metteya, ordained 1901) and the German musician Anton Güth (Nyanatiloka, 1904) became monks. The latter, having settled in Ceylon, translated Pali texts, popularized Buddhism, and most importantly, ordained subsequent Western Buddhist monks. Many of them and their successors became distinguished promoters of Theravada and its meditation technique, vipassana. The paper presents the profiles of selected Western Theravada monks, both pioneering and contemporary ones. Particular attention is paid to the circumstances and motivations accompanying the decision to radically change one’s lifestyle, taking into account a critical evaluation of Western culture.